The effect of an evidence‐based medicine course on medical student critical thinking. Issue 4 (24th May 2017) - Wang, Jing; Wang, Danhua; Chen, Yanling; Zhou, Qin; Xie, Hong; Chen, Jin; Li, Youping
Abstract: Objective: Evidence‐based medicine (EBM) was designed to foster student critical thinking (CT) while conveying knowledge to them. Chinese medical schools have adopted EBM to a varying degree but studies to examine its intended effect are few. This study evaluates the effect of an EBM course on Chinese medical student CT. Methods: A total of 158 medical students at a Chinese medical school took a seven‐category Chinese version of the critical thinking disposition inventory (CTDI‐CV) before and after taking an EBM course. Two‐tailed, paired t ‐test measured the course effect. Results: Undergraduate (BS) students showed a significant mean difference (MD) in confidence (MD = 1.43, P = 0.025), inquisitiveness (MD = 1.23, P = 0.041), and overall score (MD = 3.45, P = 0.000). Graduate (MS) students showed a more significant mean difference in confidence (MD = 2.72, P = 0.006). Moreover, BS student course grade was correlated with truth‐seeking ( r = 0.214, P = 0.029) and open‐mindedness ( r = 0.246, P = 0.012) while that of MS student was correlated with systematicity ( r = 0.295, P = 0.031) and overall score ( r = 0.290, P = 0.033). Conclusions: The results indicate some positive effect of an EBM course on student CT due to embedded CT elements in delivering the content. The discrepancy between a higher admission test score and weaker confidence shown by MS students reveals a drawback of the test centered Chinese education system.